Methane cycling in a eutrophic lake characterised by multiple stable isotope and flux measurements [data] - Schroll, Moritz (Universität, 2022)
Recent estimations demonstrate that methane (CH4) emissions from aquatic systems are responsible for up to half of global CH4 emissions. Lakes repr...